DEVELOPMENT OF ECOLOGICAL CULTURE (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
In this article, the speech goes on about forming ecological culture in the youth, expression of the issues as defending ecology and nature, processes of its historical development and future in the system of humanities.